Making climate-smart agriculture work for women farmers and entrepreneurs - Rubin, Deborah; Ajayi, Oluyede C. (Technical Centre for Agricultural and Rural Cooperation, 2019)
Women can access information about CSA through accessible communication channels like mobile phones